Factors affecting the price of corporate Islamic bonds in Indonesia, January 2010 - July 2015 - Rosida Dwi Ayuningtyas (Department of Islamic Economics, Islamic University of Indonesia, 2017)
This study aims to determine partial and simultaneous influence of interest rates on deposits, deposits of mudaraba, the price of state shari'a securities (SBSN), Rupiah exchange rate against US Dollar, and the Index of Industrial Production on the price of corporate Islamic bonds in Indonesia, for short-term or long-term period. Data are obtained from published reports of Bank Indonesia, Central Bureau of Statistics (BPS), ICAMEL library, Indonesian Capital Market Electronic Library during January 2010 to July 2015, and web support providing the price of Islamic bonds data. Corporations that become the objects of this research are PT. Listrik Negara (PLN), PT. Indosat, Tbk, and PT. Bank Muamalat Indonesia. The results using Error Correction Model (ECM) at PT. Perusahaan Listrik Negara show that variables affecting the price of Islamic bonds in short-term period are Shari’a Securities (SBSN), Index of Industrial Production, shari’a securities (SBSN) and bond prices in the previous month, while in long-term period, variables that affect the price of Islamic bonds are shari’a securities (SBSN) and Index of Industrial Production. As for PT. Indosat, variables that affect price of Islamic bonds in short-term period is the profit share of deposits, while in long-term period, they are the interest rate of deposits and the Index of Industrial Production. As for PT. Bank Muamalat Indonesia, variables that affect the price of Islamic bonds in short-term period is the deposits, the State Shari’a Securities, the previous price, and the previous deposit rates, while in the long-term period, they include the outcome of deposits, and state shari’a securities.